2010
DOI: 10.1121/1.3377116
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual interactions in the loudness of combined auditory and vibrotactile stimuli

Abstract: The loudness of auditory (A), tactile (T), and auditory-tactile (A+T) stimuli was measured at supra-threshold levels. Auditory stimuli were pure tones presented binaurally through headphones; tactile stimuli were sinusoids delivered through a single-channel vibrator to the left middle fingertip. All stimuli were presented together with a broadband auditory noise. The A and T stimuli were presented at levels that were matched in loudness to that of the 200-Hz auditory tone at 25 dB sensation level. The 200-Hz a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…Wilson et al (2010a,b) found some evidence for critical-band filtering in the vibrotactile sense in studies exploring the perceptual integration of both threshold-level and supra-threshold auditory and tactile sinusoidal signals. The differences in detection associated with the frequency spacing of auditory and tactile tones (Wilson et al, 2010a) have been mirrored in differences in the loudnesses of auditory-tactile complexes (Wilson et al, 2010b). Furthermore, the results of both of these studies indicate that critical-band filtering is exhibited in both modalities but that the auditory filters are more sharply defined than the tactile filters.…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations
“…Wilson et al (2010a,b) found some evidence for critical-band filtering in the vibrotactile sense in studies exploring the perceptual integration of both threshold-level and supra-threshold auditory and tactile sinusoidal signals. The differences in detection associated with the frequency spacing of auditory and tactile tones (Wilson et al, 2010a) have been mirrored in differences in the loudnesses of auditory-tactile complexes (Wilson et al, 2010b). Furthermore, the results of both of these studies indicate that critical-band filtering is exhibited in both modalities but that the auditory filters are more sharply defined than the tactile filters.…”
Section: Discussionmentioning
confidence: 52%
“…For our tactile experiments, stimuli were presented at 25 dB SL relative to the absolute detection thresholds for the 250 and 400 Hz vibratory signals presented to the left middle finger. For young adults, absolute detection thresholds for vibrotactile signals presented through the tactile device used here are À29 dB re 1 micron at 250 Hz and À18 dB re 1 micron at 400 Hz (Wilson et al, 2010b). When presented at a level of 25 dB SL, 250 -and 400-Hz signals are closely matched in loudness (Verrillo et al, 1969;Wilson et al, 2010b).…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…One such example is that the combination of auditory and tactile stimulation facilitates detection of a stimulation (Wilson et al, 2010a). Another example is that the combination of auditory and tactile stimulation result in greater perception of loudness than auditory stimulation alone (Wilson et al, 2010b).…”
Section: Multi-sensory Loudness Integrationmentioning
confidence: 99%